ANALISA KERUSAKAN TRANSMITTER 2 PADA LOCALIZER 05 MERK THALES TYPE 421 DI PERUM LPPNPI CABANG MEDAN - Nadira, Nadira Armelya Kaban; Arif, Muhammad Arif Sulaiman; Nurul, Nurul Hidayah; Fadly, Hendri Fadly (Cipta Kind Publisher, 2023)
On The Job Training is a University Tridharma (teaching, research and practice) activity which aims to improve teaching and increase the vision and scope of certain activities in the field, as well as improving the welfare of society and students. OJT must be carried out by Curug Indonesian Aviation Polytechnic Cadets to increase the learning outcomes obtained from their training so far and increase opportunities to explore various learning outcomes. work This is reflected in the work environment and context, as well as the ability to produce the skills and knowledge expected of professionals, especially aeronautical engineers. The tool that can overcome this problem is the Instrument Landing System (ILS). Indonesia has an aircraft navigation system called the Instrument Landing System. ILS is also an aircraft navigation system that uses radio waves as an (invisible) instrument that pilots use to guide their aircraft when approaching and landing at an airport. ILS consists of three sub systems, namely Localizer, Glide Slope, and Marker Beacon. The localizer is one of the devices contained in the Instrument Landing System whose function is to provide information regarding the plane's alignment with the runway. Position is one of the instruments in the instrument position system that provides information about the position of the aircraft on the runway. To support this communication performance, namely by ensuring that the localizer equipment runs smoothly and requires a Remote Control Monitoring System (RCMS) for Monitoring.